2021
DOI: 10.1016/j.clgc.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival After Treatment of Localized Prostate Cancer With Proton Beam Therapy, External-Beam Photon Therapy, or Brachytherapy

Abstract: With limited high-level evidence, we carried out a comparative effectiveness study for the effect of proton beam therapy (PBT) on overall survival compared to external-beam radiotherapy (EBRT) and brachytherapy (BT) among patients with localized prostate cancer using a national database. PBT was associated with a significant overall survival benefit compared to EBRT and had a similar performance as BT. Background: There are few comparative outcomes data regarding the therapeutic delivery of proton beam therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Among group 2 cancers, racial disparities in PBT receipt were significant for prostate and breast cancers, the group 2 cancers most frequently treated with PBT, 57 as well as lung and esophagus cancers. Our results are similar to those of older studies that reported racial disparities in receipt of PBT for prostate 7 , 10 , 17 , 25 , 28 and breast cancer. 17 , 26 In prostate cancer, previous studies have shown that White men who reside in more affluent regions and are diagnosed with lower-risk prostate cancer (for which RT provides no survival advantage over active monitoring) 77 are more likely to receive PBT, 7 raising concerns about overtreatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Among group 2 cancers, racial disparities in PBT receipt were significant for prostate and breast cancers, the group 2 cancers most frequently treated with PBT, 57 as well as lung and esophagus cancers. Our results are similar to those of older studies that reported racial disparities in receipt of PBT for prostate 7 , 10 , 17 , 25 , 28 and breast cancer. 17 , 26 In prostate cancer, previous studies have shown that White men who reside in more affluent regions and are diagnosed with lower-risk prostate cancer (for which RT provides no survival advantage over active monitoring) 77 are more likely to receive PBT, 7 raising concerns about overtreatment.…”
Section: Discussionsupporting
confidence: 90%
“…After further matching on health insurance coverage type or income, racial disparities in receipt of PBT narrowed but were not eliminated, suggesting that other factors may contribute to these disparities, such as practitioner referral patterns 10 , 25 , 28 ; practitioner implicit bias, 10 , 28 whereby practitioner treatment recommendations may be influenced by a patient’s race 94 , 95 , 96 ; and patient experiences of discrimination while interacting with the health care system. 97 Increased diversity and training among health care professionals could improve sensitivity to cultural contexts 98 and increase support to strategies that foster systemic changes necessary for equitable access to care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the extended time-period required for survival analyses in patients with LPCa [ 20 ], we explored the clinical significance of our data using the PRAD dataset. In this database, information from 498 primary tumor samples is available for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The overall survival of localized prostate cancer patients treated with PT, photon-based EBRT, and brachytherapy in the US between 2004 and 2015 were analyzed and compared by Liu et al [ 89 ]. They concluded that PT was associated with a significant overall survival benefit compared to EBRT, and delivered outcomes were similar to brachytherapy.…”
Section: Potential Clinical Benefits and Cost Effectiveness Of Pt In ...mentioning
confidence: 99%